The Influence of Paylater Usage on Consumerism Behavior: The Moderating Role of Cultural Values - Ulfa, Ulfa Utari; uswatun, Uswatun Hasanah; Tari, Riantari Maharani; Nisa, Anisha Hardianti (Cattleya Darmaya Fortuna, 2025)
This study aims to examine the effect of PayLater usage on consumerism behavior, with cultural values as a moderating variable. As PayLater services continue to grow as part of financial technology, their influence on consumer behavior—particularly in promoting impulsive and excessive spending—warrants deeper investigation. Using a quantitative and explanatory research approach, data were collected through an online questionnaire distributed to 116 respondents with prior experience using PayLater services. Data analysis was conducted using moderation regression with PROCESS Macro Model 1 on SPSS version 26. The results indicate that PayLater usage has a significant positive effect on consumerism behavior (p < 0.05). Cultural values also show a significant direct influence on consumerism. Interestingly, the interaction between PayLater usage and cultural values was found to be statistically significant, indicating a moderating effect. However, rather than weakening the relationship, cultural values in this context were found to strengthen the influence of PayLater usage on consumerism. This suggests that the cultural values internalized by respondents may not necessarily reflect financial restraint or frugality, but rather emphasize social norms, lifestyle conformity, or prestige. These findings contribute to a deeper understanding of consumer behavior in the digital age and highlight the importance of considering cultural contexts when analyzing the impact of financial technology on individual financial behavior.